Monday

April 21, 2014

April 21, 2014

Posted by **SAMANTHA** on Sunday, April 15, 2012 at 3:53pm.

help me!!!

- MATH -
**Bosnian**, Sunday, April 15, 2012 at 4:33pmx ^ 2 - 3 x + 2 + ( 5 x ^ 2 - 3 x -8 ) )=

x ^ 2 + 5 x ^ 2 - 3 x + ( - 3 x ) + 2 + ( - 8 ) =

6 x ^ 2 - 3 x - 3 x + 2 - 8 =

6 x ^ 2 - 6 x - 6 =

6 ( x ^ 2 - x - 1 )

**Related Questions**

Math - Can someone please check my answers below for accurateness? The ...

algebra1/McDougal Littell - I need to know how to work this problem and show my ...

Math - AlgebrAic factorization 1)6(2a-3)(a+7)+18(2a-3)(3a+2) 2) (3x-4)(5x+1)-(...

Algebra - What is the sum of all coefficients of the polynomial? f(x)= (3x^3 - ...

calculus derivatives - Please confirm: {(5x+2)^4/x^2-3x+1)^3}= 20(5x+2)^2(x^2-3x...

Math - Factor each expression. Please show me how to do it. Thanx 8x^2-10x+3 15X...

math - Logarithm 3^3x+1=3^5x-2 3^3x+1-3^5x-2=0 Log(3^3x+1-3^5x-2)=log0 Please ...

Math - Please show the solutions! 1.) x+y-2(2x-3y) 2.) x+y/2 - 3x-y/4 + x-5y/8 3...

math - what is the sum of (x^2-3x+2) and (5x^2-3x-8)? how would you solve this...

math - simplify (x^2-3x+6)-(36x^2-18x+6/6) (x^2-3x+6)-(6(6x^2-3x+1/6) cancel the...